PELATIHAN KETERAMPILAN CONTENT CREATOR BAGI ANAK ASUH PANTI ASUHAN AHMAD YANI PONTIANAK - Dedi Saputra; Wanty Eka Jayanti; Eva Meilinda; Weishky Steven Dharmawan (Mafaza : Jurnal Pengabdian Masyarakat, 2022)
This Community Service activity, which is one of the Tri Dharma, aims to add insight and provide skills in creating content designs or social media content that is interesting, interactive and easy for the foster children of the Ahmad Yani Pontianak Orphanage. The method used is to provide theory and training as practical activities. The application used is the Canva application which is easy and free to use. The participants, especially the orphanage children, were very grateful to the team from the university for developing informatics facilities that had provided training and more understanding to become content creators. Participants gain an understanding of utilizing social media in particular as a source of income. Participants can understand how to start social media properly and correctly in the role of content creator. This activity is a capital to channel talent and potential in the field of graphic design, so that you have the opportunity to be creative in the digital world and can be increased to become an opportunity to earn income.